Association between Social-Cultural and the Utilization of Elderly Integrated Health Services (Posyandu Lansia) in Hamparan Perak Health Center (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
Abstract Elderly Integrated Health Service (Posyandu Lansia) is an integrated service post for elderly in certain areas that have been agreed upon, which are community driven. A significant elderly population will be accompanied by various problems and will affect various aspects of life especially health. Based on preliminary data, the number of elderly population of 930 people, but only about 230 people or about 24.7% who came to Elderly Integrated Health Services. The purpose of this research was to analyze the association between socio-cultural and the utilization of Elderly Integrated Health Services. The type of this research is the explanatory survey with research population of 160 people and research sample of 60 respondents. Data collection used questionnaire. The results of this study were there was a correlation between tradition (p = 0.000), belief (0.001) with the utilization of Elderly Integrated Health Services. Abstrak Posyandu Lansia adalah pos pelayanan terpadu untuk orang tua di daerah tertentu yang telah disepakati, yang digerakkan oleh masyarakat. Populasi lansia yang signifikan akan disertai dengan berbagai masalah dan akan mempengaruhi berbagai aspek kehidupan khususnya kesehatan. Berdasarkan data awal jumlah populasi lansia sebanyak 930 orang tetapi yang datang ke posyandu lansia hanya berkisar 230 orang atau sekitar 24,7%. Tujuan dari penelitian ini adalah untuk menganalisis hubungan social budaya dengan pemanfaatan posyandu. Jenis penelitian ini adalah survey explanatory dengan populasi penelitian 160 orang dan sampel penelitian 60 responden. Pengumpulan data dengan menggunakan kuesioner. Hasil penelitian ini menunjukkan ada hubungan antara tradisi (p=0,000), kepercayaan (0,001) dengan dengan pemanfaatan Posyandu.